IMPLEMENTATION OF INCLUSIVE EDUCATION IN MADRASAH ALIYAH NEGERI 3 MEDAN - Suhendri Suhendri; Rijal Sabri; Muhammad Iqbal Hasibuan (Universitas Dharmawangsa Medan, 2020)
The results of this study revealed thatinclusive education planning in MAN 3 Medan was carried out by involving teachers andother education personnel before the process of accepting new students. Theimplementation of inclusive education in MAN 3 Medan has been running wheremadrasa receive students with special needs and provide adequate education services.Evaluation of inclusive education in MAN 3 Medan includes evaluation of context,input, process and results. Based on the results of this study, it is deemed necessary tomake policies on inclusive education and assist madrasas in implementing it.